Teaching Writing Skill by Using Think Pair Share Technique - Mirna Lisna Santika; Usman Kasim; Burhansyah Burhansyah (Research in English and Education Journal, 2022)
This research belongs to a library research. This study aims to figure out whether teaching writing skill using think pair share technique is effective or not according to some literatures. Meanwhile, the objects of this study are theories and literatures about the effectiveness of using TPS in teaching writing ability. The researcher used library research as the method in this study. There are five literatures in the forms of journal articles related to the topic of this research as the references to collect the data. In collecting data, the researcher used content analysis. First, the writer searched out some references such as books, journals, and articles. Then, the writer read and selected the needed data based on the research objective. After reviewing five references of previous studies regarding the effectiveness of using TPS to teach writing, the writer concluded that each literature proved that Think Pair Share technique is an effective technique to teach writing skill, it can be seen from the result of observation, the students’ result of every cycle, and the students’ score in pre-test and post-test. The writer suggests teachers should train and enhance students’ writing interest by giving interesting writing materials. Teachers should use time allocation effectively in order to make the teaching learning process able to be used maximally.